2014
DOI: 10.1037/a0036089
|View full text |Cite
|
Sign up to set email alerts
|

What makes a group worth dying for? Identity fusion fosters perception of familial ties, promoting self-sacrifice.

Abstract: We sought to identify the mechanisms that cause strongly fused individuals (those who have a powerful, visceral feeling of oneness with the group) to make extreme sacrifices for their group. A large multinational study revealed a widespread tendency for fused individuals to endorse making extreme sacrifices for their country. Nevertheless, when asked which of several groups they were most inclined to die for, most participants favored relatively small groups, such as family, over a large and extended group, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
247
0
23

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 234 publications
(285 citation statements)
references
References 47 publications
7
247
0
23
Order By: Relevance
“…To characterize individuals who are ready to initiate and engage in extreme progroup behaviors and not merely follow group norms or others' orders, Swann and colleagues (Swann, Gómez, Seyle, Morales, & Huici, 2009;Swann, Jetten, Gómez, Whitehouse, & Bastian, 2012) proposed the group identity fusion construct. For fused people, their group becomes a personal matter, and in-group members are treated as extended family, especially when common values and other characteristics are highlighted (Swann et al, 2014). The state of identity fusion depicts a feeling of oneness with a group and the merger of personal and social identities.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize individuals who are ready to initiate and engage in extreme progroup behaviors and not merely follow group norms or others' orders, Swann and colleagues (Swann, Gómez, Seyle, Morales, & Huici, 2009;Swann, Jetten, Gómez, Whitehouse, & Bastian, 2012) proposed the group identity fusion construct. For fused people, their group becomes a personal matter, and in-group members are treated as extended family, especially when common values and other characteristics are highlighted (Swann et al, 2014). The state of identity fusion depicts a feeling of oneness with a group and the merger of personal and social identities.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, fusion theory and methods had only been tested in classroom, laboratory, and online studies: revealing how personal and group identities collapse into a unique identity to generate a collective sense of invincibility and special destiny, especially when the collective is conceived as a small tight-knit group of fictive kin (7). In-depth case and field studies of terrorist groups, of how they developed and how their attacks germinated, also indicate that militants kill and die "for each other.…”
mentioning
confidence: 99%
“…Crucially, the notion of favoring one's ingroup is a key component of how “fused” people are to their social group, with people who are fused exhibiting more prosocial behaviors toward ingroup members (Swann & Buhrmester, 2015; Swann, Gomez, Dovidio, et al., 2010; Swann, Gomez, Huici, et al., 2010; Swann et al., 2014). However, the mechanisms in the brain that might mediate the influence of our affiliation to a group on our responses to the behavior of another person, have not previously been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated that identity fusion is a powerful motivator of personally costly, progroup behaviors (Whitehouse, McQuinn, Buhrmester, & Swann, 2014; Whitehouse et al., 2017). For example, strongly fused individuals report more willingness to fight and die for their groups (Swann et al., 2014); are especially inclined to endorse sacrificing their lives for fellow in‐group members (but not out‐group members) in trolley dilemma scenarios (Swann, Gomez, Huici, Morales, & Hixon, 2010); and are especially likely to donate personal funds to support group members in difficulty (Buhrmester, Fraser, Lanman, Whitehouse, & Swann, 2015; Swann, Gomez, Dovidio, Hart, & Jetten, 2010). However, how the neural correlates of the fairness of another's actions are modulated by group membership, and how such a modulation may depend on the degree to which one is fused to one's group are poorly understood.…”
Section: Introductionmentioning
confidence: 99%